Kesetaraan Gender Dalam Pendidikan Menurut Perspektif Faqihuddin Abdul Kodir - Desti Damayanti P; Faras Tetra R; Hisny Fajrussalam; Shifa Aulia R; Tasya Syafanisa (Yayasan Daarul Huda Kruengmane, 2023)
God created gender while humans created gender differences. The gender difference between men and women is not a problem if they are treated fairly, but it becomes a problem if people have different views that women's education should be lower than that of men. With this difference, there are many inequalities that occur in women, especially in the field of education. This research method is a qualitative research type with a literacy study design. The research was conducted to find out Faqihuddin Abdul Kodir's views regarding gender equality in the field of education using reading sources that have been collected.